IMPROVING THE QUALITY OF EDUCATION WITH THE HELP OF DIDACTIC COMPLEXES - Djuraeva Ra’na Bakhrombekovna (International Engineering Journal For Research & Development, 2020)
The article discusses in more detail the purpose and content of the EUMC structural components by the example of the manual on the discipline "Computer Science Information Technology" for students enrolled in the specialty of ekonomiki and religious studies